Long range planning : - Bremer, Suzanne W. (Neal-Schuman Publishers, 1994)
Planning process: what you need to get it done -- Planning committee -- Library and the community -- Taking inventory -- Public library's mission -- Roles of the public library -- Setting goals and targeting objectives -- Keeping score -- Writing the plan -- Living with your plan.